DETECTION OF PROCEDURAL ERRORS DURING ROOT CANAL INSTRUMENTATION USING CONE-BEAM COMPUTED TOMOGRAPHY (CIPEEX, 2025)
This study investigated procedural errors occurring during root canal preparation with nickel-titanium (NiTi) instruments, using cone-beam computed tomography (CBCT) imaging. Materials and Methods: A total of 100 human mandibular molars were divided into five groups (n = 20) according to the NiTi system used for root canal preparation: Group 1 - BioRaCe, Group 2 - K3, Group 3 - ProTaper, Group 4 - Mtwo, and Group 5 - Hero Shaper. CBCT images were obtained to detect procedural errors committed during root canal preparation. Two examiners evaluated the presence or absence of fractured instruments, perforations, and canal transportation. The chi-square test was used for statistical analysis. The level of significance was set at α=5%.
Keywords: Cone-beam computed tomography; diagnostic imaging; root canal preparation; rotary instruments